2010
DOI: 10.1088/0953-8984/22/5/055901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manganese doping on the size effect of lead zirconate titanate thin films and the extrinsic nature of ‘dead layers’

Abstract: Abstract:We have investigated the size effect in lead zirconate titanate (PZT) thin films with a range of manganese (Mn) doping concentrations. We found that the size effect in the conventional Pt/PZT/Pt thin-film capacitors could be systematically reduced and almost completely eliminated by increasing Mn doping concentration. The interfacial layer at the electrode-film interface appears to disappear almost entirely for the PZT films with ~2% Mn doping levels, confirmed by the fits using the conventional "in-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
1
18
1
Order By: Relevance
“…This is attributed to the presence of an interfacial dead layer between the ferroelectric and metallic electrode, similar to what reported for other ferroelectric thin films, such as PZT, 32 Ba͑Zr 0.25 Ti 0.75 ͒O 3 , 28 and ͑Ba, Sr͒TiO 3 . This is attributed to the presence of an interfacial dead layer between the ferroelectric and metallic electrode, similar to what reported for other ferroelectric thin films, such as PZT, 32 Ba͑Zr 0.25 Ti 0.75 ͒O 3 , 28 and ͑Ba, Sr͒TiO 3 .…”
Section: B Dielectric and Piezoelectric Characterizationsupporting
confidence: 84%
“…This is attributed to the presence of an interfacial dead layer between the ferroelectric and metallic electrode, similar to what reported for other ferroelectric thin films, such as PZT, 32 Ba͑Zr 0.25 Ti 0.75 ͒O 3 , 28 and ͑Ba, Sr͒TiO 3 . This is attributed to the presence of an interfacial dead layer between the ferroelectric and metallic electrode, similar to what reported for other ferroelectric thin films, such as PZT, 32 Ba͑Zr 0.25 Ti 0.75 ͒O 3 , 28 and ͑Ba, Sr͒TiO 3 .…”
Section: B Dielectric and Piezoelectric Characterizationsupporting
confidence: 84%
“…The dielectric properties of ferroelectric perovskite thin films are known to be influenced by many effects, such as grain size, grain boundaries, film thickness, etc . In general, a reduction in the thickness and the grain size leads to a decrease in the dielectric permittivity and an increase in the dielectric losses in thin films .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Lou and Wang found that the "dead layer" between Pt and Pb(ZrTi)O 3 is extrinsic and could be removed almost completely by doping 2% Mn. 59 Experimentally, many researchers found that SRO/BTO/SRO capacitors (as well as other perovskite FE structures with conductive oxide electrodes) are free from passive layers. 31,60,61 Recently, a very interesting experimental result demonstrates that the RuO 2 /BaO terminations at BTO/SRO interface, which is assumed as many pinned interface dipoles and plays a detrimental role in stabilizing a switchable FE polarization, can be overcome by depositing a very thin layer of SrTiO 3 between the BTO layer and SRO electrode.…”
Section: A Size Effectsmentioning
confidence: 99%